Key concepts in urban geography - Latham, Alan. (Thousand Oaks, [Calif.] London SAGE, 2008)
With detailed entries on a selection of subjects from global cities and urban nature to translational urbanism and virtuality, this book is a useful addition to urban geography reading lists.
Includes bibliographical references and index.
Keywords: Urban geography; Electronic books